2015
DOI: 10.17305/bjbms.2016.660
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of three different regimens against Helicobacter pylori as a first-line treatment: A randomized clinical trial

Abstract: Treatments with bismuth-containing quadruple therapy (QT), sequential therapy (ST), or concomitant therapy (CT) have been proposed as empirical first-line regimens for Helicobacter pylori. We compared the efficacy and tolerability of 10 days bismuth-containing quadruple QT, 10 days ST, and 10 days CT with as first-line treatments for H. pylori in a randomized crossover study. The subjects were randomly divided into three groups. The first 130 patients were treated with rabeprazole, bismuth potassium citrate, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 39 publications
1
32
0
1
Order By: Relevance
“…Recent studies have carried out randomized trials including bismuth-containing quadruple therapy, widely used as a second-line eradication therapy 23,35. In this trial, we compared all three currently used therapeutic regimens: 7d-TT, 10d-CT, and 10d-ST.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have carried out randomized trials including bismuth-containing quadruple therapy, widely used as a second-line eradication therapy 23,35. In this trial, we compared all three currently used therapeutic regimens: 7d-TT, 10d-CT, and 10d-ST.…”
Section: Discussionmentioning
confidence: 99%
“…ST was effective in case of clarithromycin resistance,39 metronidazole resistance,40 and even resistance to both clarithromycin and metronidazole 39. ST was reported to be more effective than 7d-TT in many Asian countries 35. However, the shortcoming of ST is that medications were changed during treatment and patients found it difficult to take them 32.…”
Section: Discussionmentioning
confidence: 99%
“…Curing H. pylori infection still remains a challenge in clinical practice. The 10-day sequential therapy, suggested as first-line therapy in the current Italian guidelines [3], has been proven to be effective in several countries, achieving eradication rates as high as 91.1%-93.7% in Italy [7,11], 92.5-95% in Turkey [12,13], 94.2% in Slovenia [14], 90% in Portugal [15], 90% in Belgium [16], 95.9% in Israel [17], 94% in Thailand [18], 91.9% in Taiwan [19], 90.3% in Singapore [20], and 88.6% in the United Arab Emirates [21]. In detail, the 10-day sequential therapy was found to be equally effective -but cheaper -than J Gastrointestin Liver Dis, March 2019 Vol.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that CT is more effective than STT for H. pylori eradication in areas where antibiotic resistance is high. 9 , 15 In some countries, including South Korea, many clinicians prescribe CT for H. pylori eradication. However, CT has more side effects than STT, and some studies showed that probiotics were effective for the eradication of H. pylori in the Asian population including Korea.…”
Section: Discussionmentioning
confidence: 99%